Diferentes métodos de treinamento de força muscular e a variação da frequência cardíaca em adultos: um estudo piloto - Viana, Macenilzon Ribeiro (Brasil, 2023)
The objective was to analyze the acute effects of heart rate (HR) of different methods of muscle strength training (TFM) in university adults, at a Federal University of Amazonas, located in the municipality of Parintins. It was hypothesized that different training methods have different effects on HR variability. The research was experimental, applied in nature. The research population was university students from Higher Education Institutions of some universities in the city of Parintins, such as UEA; FAMETRO and ICSEZ UFAM. the selected subjects answered an anamnesis online, containing sociodemographic information, health history and time of practice in bodybuilding. The main outcome of the study was the HR measured by the Sppedo polar monitor. The people were submitted to three TFM methods, (Decreasing Pyramid; Bi-set and Rest-pause), with an interval of at least one day of rest between them. At each training session, the HR was measured after a five-minute rest, at the end of each series and again 15 minutes after the end of the session. Student's t test was used to compare HR means, adopting a significance level of 5%. At the end of three months of recruitment and selection, 11 university students participated, most of them male (n=6). The university students had an average of 25 (±3.11) years and three and a half years of experience with bodybuilding. The main health problems reported were back pain (n=5) and history of fractures and injuries (n=5). The results showed that the HR of the participants varied between the TFM methods applied and the types of physical exercises. In the decreasing pyramid training method, there was a difference (p<0.05) in the HR of the first and last training series, respectively, in the leg extension exercises (114.55±21.11 and 111.18±18.78) and flexor table (113.91±20.49 and 110.27±15.99). However, an increase in HR was also verified, in the moment before training and after the first series, in the flexor table exercise, respectively 64.82(±10.00) and 113.91(±20.49). As for the Bi-Set method, there was a difference (p<0.05) in the HR of the first and last training series, respectively, in the Leg Press 45º + sumo squat (139.00±19.60 and 153.45±20, 68) and Hack Machine 90º + stiff (146.36±26.82 and 155.91±22.26). Finally, in the Rest Pause method, there was a difference in HR from the first to the last series (4th series), respectively, on the leg extension chair (125.09(±25.85 and 145.82±22.07) and on the flexor table (127 ,91±27.13 and 136.18±23.31). In the comparison after the first series and after the 15 minutes of rest, it was possible to identify that there was a difference only in the Bi-Set and Rest Pause methods. Bi-Set, in the Leg Press exercise 45º + sumo squat (139.00±19.60 and 89.82±17.79) and in the Hack Machine exercise 90º + stiff (146.36±26.82 and 89.82± 17,79). In the Rest Pause, the HR decrease was identified only in the leg extension exercise from 125.09(±25.85)bpm after the first training series to 88.82(±11.95) bpm after 15 minutes after the end of the TFM. In view of this, it is concluded that the acute effect of different methods of TFM on the HR varies throughout the training series and after the end of the TFM. There is a significant increase between the first and last series of training and a drop in HR after 15 minutes of exercise ture of the TFM session.